Komite Nominasi dan Remunerasi dan Kinerja Perusahaan - Wiandra, Aksan Maulana; Widiastuty, Erna (Universitas Teuku Umar, 2025)
This study aims to provide empirical evidence on the influence of the Nomination and Remuneration Committee (NRC) on company performance. Using purposive sampling, the study obtained 155 firm-year observations for the period 2019–2023. The NRC variable is measured by the existence of the NRC, the number of NRC members, and the frequency of NRC meetings. Company performance is measured through accounting performance and market performance, while company size, measured by total assets, is used as a control variable. The results of the study are vary. When company performance is measured by market performance, the existence of the NRC shows a significant effect, but when company performance is measured by accounting performance, the opposite is true. In addition, the number of NRC members are positively influences company performance as measured by ROE. Lastly, the frequency of NRC meetings has an positive effect on company performance as measured by ROA, ROE, and NPM.